Relationship of knowledge and patient activity with malaria incidence - I Ketut Swastika; Saria Dewi Sartika Hutagaol (Science Midwifery, 2023)
Malaria is a life-threatening disease and can cause death. Attitudes and behaviors of respondents related to risk factors for malaria transmission and also respondents' habits in carrying out malaria prevention and treatment efforts. The purpose of this study is to determine the relationship between knowledge and patient activity with the incidence of Malaria. This research was conducted at Lukas Enembe Kabupaten Regional General Hospital Mamberamo Tengah. The research design used a cross sectional design with a sampling technique, namely total sampling with a sample of 35 respondents. The study was conducted in November 2022. The data analysis used is a chi square test with a significance value of p < (0.05). The results showed that most respondents had good knowledge about malaria (80%) and most respondents had daily activities in the good category (54.3%). Knowledge and behavior of respondents' activities related to risk factors for malaria transmission and also respondents' habits in carrying out malaria prevention and treatment efforts.